2013
DOI: 10.1371/journal.pone.0068477
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin1 Is a Negative Regulator of the Small GTPase Rac1

Abstract: The Rac1 GTPase is a critical regulator of cytoskeletal dynamics and controls many biological processes, such as cell migration, cell-cell contacts, cellular growth and cell division. These complex processes are controlled by Rac1 signaling through effector proteins. We have previously identified several effector proteins of Rac1 that also act as Rac1 regulatory proteins, including caveolin-1 and PACSIN2. Here, we report that Rac1 interacts through its C-terminus with nucleophosmin1 (NPM1), a multifunctional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Our data provide evidence for both mechanisms. LC-MS/MS identified B23 as a Rac1 nuclear interactor, and the biochemical data attest to the physiological relevance of this interaction because B23 binds most strongly to the N-terminal region of Rac1, and not exclusively through the polybasic C-terminal region, as proposed (Zoughlami et al, 2013). This finding thus excludes the trivial explanation of a purely electrostatic interaction ( Figure 2).…”
Section: Discussionmentioning
confidence: 51%
“…Our data provide evidence for both mechanisms. LC-MS/MS identified B23 as a Rac1 nuclear interactor, and the biochemical data attest to the physiological relevance of this interaction because B23 binds most strongly to the N-terminal region of Rac1, and not exclusively through the polybasic C-terminal region, as proposed (Zoughlami et al, 2013). This finding thus excludes the trivial explanation of a purely electrostatic interaction ( Figure 2).…”
Section: Discussionmentioning
confidence: 51%
“…On one hand, active Rac1 directly interacts with STAT3 and regulates its activity by promoting its phosphorylation (Simon et al, 2000). On the other hand, Rac1 interaction with nucleophosmin-1 attenuates Rac1 signaling and inhibits cell spreading (Zoughlami et al, 2013). Moreover, increased Rac1 shuttling into the nucleus accelerates cell division (Michaelson et al, 2008).…”
Section: Rho Gtpase Signaling From Nucleusmentioning
confidence: 99%
“…Another possibility is that NPM is phosphorylated at T199 in the nucleus and, thereafter, translocates from the nucleus to the cytoplasm. Of note, it has been reported that activated small GTPase Rac1, a protein that is highly relevant to HUVECs (59), may favor translocation of phosphorylated NPM from the nucleus to the cytoplasm (60). In our experimental conditions, the kinase that phosphorylates NPM at T199 and the cellular location of this phosphorylation, whether in the cytoplasm or in the nucleus, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%